Utilization of simulation for training enhancement - Olanrewaju, O. S. (IGI Global, 2013)
Engineering system design, operation, and maintenance has been handled for a long time through mathematical and real time models. The advent of computers, multimedia age, and improvement in visualization has further proved the reality of fact that picture speaks more than words; also, research in education and training has proven that visualization has a great effect on improving learning. The complexity of real world situation of engineering education has obvious limitations of instructional presentation and training. Simulation gives result from theoretical representation of complex phenomena when hardware for the task is lacking, or in situations when enough time is not available for explanation. This chapter discusses opportunities brought about by simulator as a tool in the training and certification of the Malaysian Maritime Academy cadets training program. The usefulness of simulators in a continuous education program to amplify and enhance competency-based education and instructional training to meet goals of safety, cleaner ocean, and protection of marine environment are highlighted. The chapter also presents the potential of simulators as training tools in other fields of knowledge for enhanced outcomes and competency-based education.